Efek Diet Tinggi Kolesterol Terhadap Peningkatan Kolesterol Darah, Gambaran Histopatologi Hati, dan Bobot Badan Kelinci New Zealand White Jantan - Bibi Ahmad Chahyanto; Rimbawan Rimbawan; Sri Anna Marliyati; Wiwin Winarsih (Jurnal Sain Veteriner, 2016)
This study was conducted to analyze the high cholesterol diet effect of egg yolk powder toward the increase of blood cholesterol and body weight in male New Zealand White rabbit and learned their liver histophatology figure. The experimental studies with Completely Randomized Design (CRD) used 13 male New Zealand White rabbit aged 6 – 7 months and weight 2,9 – 4,0 kg. Rabbit were divided into 3 groups: group 0 (n=4) given the standard feed, group 1 (n=4) given high cholesterol diet from egg yolk powder, and group 2 (n=5) given high cholesterol diet from egg yolk powder and red palm oil mix. The intervention was implemented for 8 weeks after 4 weeks adaptation period. The results showed that intervention of high cholesterol diet from egg yolk powder significantly increased levels of serum cholesterol and fatty liver, but did not significantly affect body weight of male New Zealand White rabbit.